Microstructure, tensile properties and thermal stability of AlMgSiScZr alloy printed by laser powder bed fusion. (10th April 2021) - Bi, Jiang; Lei, Zhenglong; Chen, Yanbin; Chen, Xi; Tian, Ze; Lu, Nannan; Qin, Xikun; Liang, Jingwei
Abstract: The new generation of Sc and Zr modified Al alloys has been attracted wide concerns in aerospace industry, owing to the excellent mechanical performances and superior thermal stability than other normal Al alloys. By microalloying with Sc and Zr, the Al3(Sc, Zr) particle forms as the grain refiner during the solidification, which is extremely beneficial for the laser powder bed fusion (LPBF) processed Al alloys. In this study, a new type Al-14.1Mg-0.47Si-0.31Sc-0.17 Zr alloy was additively manufactured by LPBF, and the microstructure, tensile properties and thermal stability were studied in detail. By using a single melt-67° scanning strategy, the LPBF-processed specimen with a relative density of 99.4 % and tensile strength of 487.7 MPa was obtained at 160 W-200 mm/s. And this AlMgSiScZr alloy can still exhibit an excellent tensile strength of 393.9 MPa at a moderate temperature of 473 K. After the aging treatment, the tensile properties further increased due to the precipitate hardening of Mg2Si and Al3(Sc, Zr), and the maximum value (580 MPa) was reached at an aging time of 10 h. The average crystal size was almost unchanged after aging treated at 325 ℃ and 24 h, indicating this AlMgSiScZr alloy has an improved thermal stability. The AlMgSiScZr alloy is recommended to substitute some particular titanium alloys in aerospace field afterwards.